ZEBRAFISH AS AN EMERGING IN VIVO MODEL IN DENTOMAXILLOFACIAL RESEARCH - Suriyah, Wastuti Hidayati; Aziza Solachuddin, Ayako; Razi Ryoshi Solachuddin, Ar (Journal of Health and Dental Sciences, 2025)
Animal models are vital in dental research for studying dentomaxillofacial anomalies, disease mechanisms, and therapeutic strategies. Conventional models, such as those using rodents and higher mammals, provide valuable insights but raise ethical, financial, and translational challenges. Zebrafish (Danio rerio), widely established in biomedical sciences, offer distinctive advantages including genetic similarity to humans, transparent embryos, rapid development, and low maintenance costs. Despite their potential, their use in dental research remains relatively limited. This review evaluates current and emerging applications of zebrafish in dentistry based on peer‑reviewed literature and institutional resources. Research highlights three main areas. In tooth and craniofacial development, zebrafish contribute insights into odontogenesis, regeneration, and congenital anomalies through continuous tooth replacement and conserved pathways such as bone morphogenetic protein (BMP) and Hedgehog. In dental material studies, zebrafish embryos serve as sensitive models for assessing systemic and craniofacial toxicity of fluorides, nanoparticles, alloys, bioceramics, and resin-based monomers. In oral cancer research, transparent zebrafish lines and xenograft models enable real-time visualisation of tumor progression, metastasis, and treatment response, supporting high-throughput drug screening. Although limitations such as the absence of permanent dentition and anatomical differences restrict direct translation, zebrafish provide a rapid, ethical, and cost-effective complement to mammalian models—advances in genetics and imaging promise to expand their role in dental research and strengthen their translational relevance. DOI : 10.54052/jhds.v5n2.p113-126